ANALISIS YURIDIS PENERAPAN HUKUM TERHADAP TINDAK PIDANA PERDAGANGAN ORANG YANG MENYEDIAKAN JASA SEKS KOMERSIAL (Studi Putusan Nomor 484/Pid.Sus/2018/PN.Sby) - Ensklopedi Sarumaha (Jurnal Panah Hukum, 2022)
Commercial Sex Service Provider is a business actor who provides or provides services by offering himself as a sexual gratification to others by expecting payment, in the form of money, for the services he has performed. One of the crimes of providing commercial sex services that have been examined and tried by the Surabaya District Court is decision number 484/Pid.Sus/2018/PN.Sby. On July 5, 2018, the perpetrator was sentenced to 1 (one) year in prison for violating Article 506 of the Criminal Code regarding the act of pimping (suonteneur), meaning the act of providing commercial sex services. The type of research used is normative legal research with an approach, legislation approach, case approach, and analytical approach. Data was collected using secondary data, which was obtained through library materials consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis used was descriptive qualitative data analysis and the conclusion was drawn using the deductive method. Based on the research findings and discussion, it can be concluded that the application of the law to the criminal act of trafficking in persons who provide commercial sex (study of decision number 484/Pid.Sus/2018/PN.Sby) is in the analysis of the judge's decision based on the decision of the Surabaya district court, stating that the perpetrator Ahmad Jawari bin Mardiono has been legally and convincingly proven guilty of committing the crime of "obscene acts" as stated in the third alternative indictment of Article 506 of the Criminal Code, where according to the author the elements of obscene acts are regulated in Article 289 of the Criminal Code, which is charged to the perpetrator. However, in the decision handed down to the perpetrator, there was a discrepancy in the application of the law with the indictment of Article 506 of the Criminal Code which was suspected of the perpetrator, not regarding obscene acts but acts of providing commercial sex services. Based on the description of the conclusion, the authors suggest that the panel of judges who examine and decide on a criminal case pay more attention to the application of the sentencing as stated in the verdict. So that judges should in examining and adjudicating a criminal case may still uphold the values ​​of justice to create a legal order that is in accordance with the criminal law code